Why Women Still Experience Unequal Digital Access and Opportunities: Comparing How Social Norms, Economic Barriers, Technology Skills, and Online Safety Challenges Shape the Gender Digital Divide in Indonesia and Zimbabwe - Suharnanik, Suharnanik; Suud, Mohammad; Harianto Cipta Utama, Yudi; Kushata, Cindy; Blessing Chainaimoyo Change (International Journal of Education, Vocational and Social Science, 2026)
The gender digital divide remains a multidimensional challenge across the Global South, particularly for women in Indonesia and Zimbabwe. Using a mixed-methods design that integrates quantitative survey data with qualitative interviews, this study examines how social norms, economic barriers, technological skills, and online safety risks shape women’s unequal digital access and participation in both national contexts. The findings reveal significant structural disparities: Zimbabwe records lower internet penetration (59.1%) and a wider gender gap (15%), with only 45% of women possessing basic digital skills, while 78.9% cite the high cost of data and 55.3% report poor connectivity as major barriers. In contrast, Indonesia demonstrates higher internet penetration (73.7–79.5%) and a smaller gender gap (1–3%), yet women remain disadvantaged in advanced digital competencies, productive digital engagement, and online safety, with 45% reporting experiences of gender-based online violence. Drawing on Cyberfeminist theory, the study illustrates the ambivalent nature of digital technologies, which simultaneously offer new avenues for empowerment while reproducing patriarchal control, objectification, and gendered surveillance. An intersectional analysis further reveals that women who are poor, less educated, or residing in rural areas face compounded forms of digital exclusion due to the overlapping effects of gender, socioeconomic status, and geographic marginalization. The study concludes that expanding internet access alone is insufficient to bridge the gender digital divide; targeted interventions must include gender-responsive digital literacy initiatives, robust online safety protections, supportive policy frameworks, and community-based empowerment ecosystems. By comparing Indonesia and Zimbabwe, the study highlights that despite contextual differences, both countries share underlying structural patterns of inequality, underscoring the need for cross-country learning and coordinated strategies to promote safer and more inclusive digital futures for women.